Advances in Lithium‐Containing Anodes of Aprotic Li–O2 Batteries: Challenges and Strategies for Improvements. Issue 8 (18th July 2017) - Song, Hucheng; Deng, Han; Li, Chao; Feng, Ningning; He, Ping; Zhou, Haoshen
Abstract : Lithium metal for rechargeable aprotic Li–O2 batteries is considered one of the most fascinating anode materials that can deliver high theoretical specific capacity, low density, and low negative electrochemical potential. Although lithium‐metal anodes have been studied extensively for decades, the cycling performance of rechargeable aprotic Li–O2 batteries based on lithium‐metal anodes is rather poor because of the unresolved security issues related to lithium dendrites and contaminant (O2, H2 O) crossover from cathode to anode. Here, the critical issues and challenges facing lithium‐containing anodes associated with the security, stability, and efficiency are analyzed. Moreover, the latest research progress and strategies used to improve the performance of aprotic Li–O2 batteries based on lithium‐containing anode are reviewed. Perspectives toward the development of highly stable lithium‐containing anodes are also presented. Abstract : Contaminants (O2, H2 O) attacking the anode and lithium‐dendrite growth are regarded as the two main challenges that exist in lithium anodes for Li–O2 batteries. An overview of recent progress and future directions for anode protection, including alternative anodes, surface passivation, and protective films, as well as solid‐state electrolytes, to improve the cycle performance of Li–O2 batteries, are presented.